Anmeldelser - Hauge, Peter (Danish Yearbook of Musicology, 2004)
Review of: Johann Schop: Erster Theil newer Paduanen, ed. Arne Spohr (Recent Reseaches in the Music of the Baroque Era, 125). Middleton, Wis.: A-R Editions